2021
DOI: 10.1002/rcm.9069
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of single‐cell microbial mass spectra profiles from single‐particle aerosol mass spectrometry

Abstract: Rationale Single‐particle aerosol mass spectrometry is a practical method for studying microbial aerosols. However, the related mass spectral characteristics of single‐cell microorganisms have not yet been studied systematically; hence, further investigations are necessary. Methods Different microbial cells were grown and directly aerosolized in the laboratory. These aerosols were then drawn into a single‐particle mass spectrometer platform, and single‐cell mass spectra profiles were obtained in real‐time. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…We utilize MD simulations to rationalize this and found that some of the transmembrane regions which maintain their helicity at high temperatures are prone to fragmentation, giving credence to our hypothesis that protons can both stabilize and induce successive peptide bond cleavage through migration along the protein backbone, resulting in the fragmentation patterns observed above. The ability to extract structural information from native top‐down MS of soluble and membrane proteins has been demonstrated using various activation modalities, so it is conceivable that an enduring influence of the protein ion structure is reflected in the distribution of product ions [14d,17,18e–f,41] …”
Section: Discussionmentioning
confidence: 99%
“…We utilize MD simulations to rationalize this and found that some of the transmembrane regions which maintain their helicity at high temperatures are prone to fragmentation, giving credence to our hypothesis that protons can both stabilize and induce successive peptide bond cleavage through migration along the protein backbone, resulting in the fragmentation patterns observed above. The ability to extract structural information from native top‐down MS of soluble and membrane proteins has been demonstrated using various activation modalities, so it is conceivable that an enduring influence of the protein ion structure is reflected in the distribution of product ions [14d,17,18e–f,41] …”
Section: Discussionmentioning
confidence: 99%
“…SPMS single-step laser desorption is a difficult ionization process in which organic compounds produce ion fragments of different degrees. Liu et al [37] used Bacillus thuringiensis to explore the influence of different laser pulse energies on SPAMS and found that particles do not ionize when the laser energy is lower than 0.2 mJ•pulse −1 and that the ionic peak increases significantly when the laser energy is higher than 1.5 mJ•pulse −1 ; they also found that particle integrity is the best when the laser energy is about 0.5 mJ•pulse −1 . Too-high or too-low energy is not conducive to the discovery of the characteristic mass spectrum.…”
Section: Influence Analysis Of Laser Energymentioning
confidence: 99%
“…Through this method, environmental particles with both dust and characteristic biological spectra fingerprints were successfully excluded from the classification of biological particles. Liu et al (2021) used Bacillus thuringiensis to explore the influence of different laser pulse energies on SPAMS and found that particles did not ionize when the laser energy was lower than 0.2 mJ and that the ionic peak increased significantly when the laser energy was higher than 1.5 mJ; they also found that the ionic peak integrity was the best when the laser energy was about 0.5 mJ. Too high or too low energy was not conducive to the discovery of the characteristic mass spectrum.…”
Section: Influence Analysis Of Laser Energymentioning
confidence: 99%